Pengaruh Disiplin Kerja, Kepuasan Kerja dan Motivasi Kerja terhadap Kinerja Karyawan - Subiakto, Dhea Cecillia Loveanty; Pujianto, Surahman (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
This study aims to examine the effect of work discipline, job satisfaction and work motivation on employee performance at Kerjasama PT. XYZ.The sample in this study were 75 employees. This research uses saturation sampling technique. Data collection was carried out by distributing questionnaires to respondents and using a Likert scale. The method of data analysis in this study is multiple linear regression. Prior to testing the hypothesis, the data was analyzed by testing the research instrument, and testing the classical assumptions. Based on the results of the analysis of hypothesis testing data in this study, it shows that work discipline and work motivation have a significant positive effect on employee performance, while job satisfaction shows the results negative on t-test calculations but has no significant effect on employee performance. Therefore, company must pay serious attention to improving the work discipline and work motivation of their employees